1989
DOI: 10.1104/pp.90.3.1221
|View full text |Cite
|
Sign up to set email alerts
|

Use of Carbon Oxysulfide, a Structural Analog of CO2, to Study Active CO2 Transport in the Cyanobacterium Synechococcus UTEX 625

Abstract: Carbon oxysulfide (carbonyl sulfide, COS) is a close structural analog of CO2. Although hydrolysis of COS (to CO2 and H2S) does occur at alkaline pH (>9), at pH 8.0 the rate of hydrolysis is slow enough to allow investigation of COS as a possible substrate and inhibitor of the active CO2 transport system of Synechococcus UTEX 625. A light-dependent uptake of COS was observed that was inhibited by CO2 and the ATPase inhibitor diethylstilbestrol.The COS taken up by the cells could not be recovered when the light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 20 publications
6
38
1
Order By: Relevance
“…1). In a recent study, we have confirmed that Chl a fluorescence quenching monitors inorganic carbon accumulation by direct measurements using the silicone fluid centrifugation technique (19 (Fig. 1).…”
Section: Fluorimetrymentioning
confidence: 51%
See 3 more Smart Citations
“…1). In a recent study, we have confirmed that Chl a fluorescence quenching monitors inorganic carbon accumulation by direct measurements using the silicone fluid centrifugation technique (19 (Fig. 1).…”
Section: Fluorimetrymentioning
confidence: 51%
“…The use of COS, however, is complicated by the fact that it is broken down by CA or by intact cyanobacterial cells to CO2 and H2S (19). In this paper we demonstrate that H2S is also a potent, selective, and reversible inhibitor of active CO2 transport in the cyanobacterium Synechococcus UTEX 625.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Likewise with air-adapted Scenedesmus, the Ko.5(DIC) at pH 5 to 6 required only 5 uM CO2, but 8 times higher CO2 was needed at this pH for the Ko.5(DIC) by C02-grown cells. In addition, the CO2 pump when present in unicellular algae is inhibited by COS (19,23) or H2S (5) and by salicylhydroxamic acid in Dunaliella (14). The other DIC-concentrating mechanism in Scenedesmus is considered to be an alkaline HCO3-transporter which functions between pH 7 to 11.…”
Section: Discussionmentioning
confidence: 99%